INCREASING STUDENTS' MOTIVATION TO LEARN BY USING THE PROBLEM BASED LEARNING METHOD ON PAI SUBJECTS AT SMA NEGERI 1 SAMPANG - Khairul Walid; Irma Soraya (Ar-Raniry: International Journal of Islamic Studies, 2022)
Problem Based Learning (PBL) is one method in the learning process that can be an alternative choice solution in the learning process. What and how are the planning steps and the process of implementing the PBL method in increasing student motivation in class XI IPS 2 SMA Negeri 1 Sampang which is the background of the problem in this study which aims to obtain concrete information and steps in the planning and implementation process. the PBL method and the acquisition of student learning scores in increasing student motivation in class XI IPS 2 SMA Negeri 1 Sampang. The research method used is a qualitative approach method. The results of this study concluded that active learning in class XI IPS 2 SMA Negeri 1 Sampang includes three aspects, namely; Cognitive skills, namely initiative, activeness, cooperation, accuracy in answering students have scores above the PP-completeness of 83%. Affective; acceptance, participation, assessment/determination of character, and organization whose percentage of completeness is above 83.33%. Psychomotor; children's movements include perception, readiness, guided movements and complex movements based on observations that show that children follow well by 78.34%.